Myofibroma of the mandible – Case report. Issue 1 (April 2016) - Castro, Hércules Henrique Onibene; Gomes, Hayder Egg; Tassara, Luiz Felipe Rossi; de Freitas, João Batista; Grandinetti, Helenice de Andrade Marigo; Capistrano, Herminia Marques
Abstract: Background: Myofibroma is a benign mesenchymal neoplasm consisting of myofibroblasts proliferation. It is uncommon in the oral cavity and only a few cases were reported about the solitary myofibroma within the mandible. Methods: This article is reporting a case of central myofibroma involving the right side of the mandible of a 13-year-old girl with the clinical, radiologic, histological and immunohistochemical management for diagnosis and treatment. Results: The clinical and imaginological aspects suggested a widespread odontogenic and non odontogenic lesions In the histopathological examinations, a biphasic pattern of the spindle and round-shaped cells was revealed. Immunohistochemical reaction was shown as positive diagnosis to Smooth Muscle Actin. These findings indicated the myofibroblastic nature of the cells. Our results provided the diagnosis of myofibroma. Conclusion: The clinical, imaginological and histological features indicated that the uncommon intraosseous myofibroma should be considered in differential diagnosis of widespread odontogenic and non odontogenic intraosseous mandibular lesions.